FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN UPAYA PENCEGAHAN PENULARAN COVID-19 DI DESA TANJUNG MERIAH KECAMATAN STTU JEHE KABUPATEN PAKPAK BHARAT - Paskah Rina Situmorang; Pebri Alianda Sikettang; Rostinah Manurung; Christina Magdalena T.Bolon (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2022)
Corona virus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Corona virus 2 (SARS-CoV-2). SARSCoV-2 is a new type of coronavirus that has never been previously identified in humans. Which can cause respiratory syndrome. This research is a quantitative research with descriptive research method. The population in this study were all heads of families in Dusun 3, Tanjang Meriah Village, totaling 287 people with a total of 68 families. And the technique of sampling is a non-probability technique, namely the Accident Sampling technique, which is a technique for determining the sample based on chance. The results showed that 16 people (53%), keeping a distance of 8 people (27%), by washing their hands, as many as 6 people (20%). Various measures have been implemented to prevent the spread of Covid -19 in Indonesia, one of which is through the 3M Movement. The 3M movement is one of the efforts currently being carried out by the government to break the chain of the spread of Covid-19 in Indonesia. These include wearing masks, social distancing, and washing hands. It is hoped that all people will continue to follow the health protocol in accordance with city and village government regulations.